If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15f + 6 + -1f = 2f + -6 Reorder the terms: 6 + 15f + -1f = 2f + -6 Combine like terms: 15f + -1f = 14f 6 + 14f = 2f + -6 Reorder the terms: 6 + 14f = -6 + 2f Solving 6 + 14f = -6 + 2f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-2f' to each side of the equation. 6 + 14f + -2f = -6 + 2f + -2f Combine like terms: 14f + -2f = 12f 6 + 12f = -6 + 2f + -2f Combine like terms: 2f + -2f = 0 6 + 12f = -6 + 0 6 + 12f = -6 Add '-6' to each side of the equation. 6 + -6 + 12f = -6 + -6 Combine like terms: 6 + -6 = 0 0 + 12f = -6 + -6 12f = -6 + -6 Combine like terms: -6 + -6 = -12 12f = -12 Divide each side by '12'. f = -1 Simplifying f = -1
| 7x-1=2x-4 | | 13t-4(2t-5)=15 | | 16y^3-4y^2-2y=0 | | 2n-6*4=5 | | (3x-7)-5=12 | | 22x=35 | | 12x=37 | | 18x-32=28x/2 | | 1w+2w=24 | | -1a=9 | | 7x+4x=8 | | 7x+7-6x=6 | | 7(x-3)-2x= | | y^3-12y^2+32=0 | | -6(m+1)-2c=24 | | 2x^6-x^4-2x^2+4=0 | | 1.14x=1.25 | | x^2+4=x+4 | | 0.25x=0.275 | | -9+16x=5x+13 | | (2x-9)+3x=16 | | 30-(-2)(4-x)= | | X+19+2x=-18-2x-23 | | 4(-0.142+-0.285y)=-13 | | (x-17.5)*9.5=8.085 | | 30-(2)(4-x)= | | 13.61=142.56x^6-635.47x^5+1196.7x^4-1235.9x^3+752.4x^2-261.81x+43.991 | | (x-17.5)*9.5=1.415 | | ifx+6=3thenx | | -3.3a=-33 | | X+17+2x=-22-2x-26 | | 8.6b=103.2 |